Nano composite oil displacement material as well as preparation method and application thereof

The oil field is modified through cavitation coupled electrochemical polarization process to inject wastewater back into the oil field, and nano-intelligent composite oil-damping materials are prepared, which solves the problems of low initial viscosity and large viscosity loss of polymer solution, and achieves efficient crude oil recovery.

CN119823744AInactive Publication Date: 2025-04-15NANJING ASSEN ENVIRONMENT TECH +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510325266.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-19
Publication Date
2025-04-15
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The initial viscosity of existing polymer solutions is low during preparation and use and the viscosity loss is large, resulting in a continuous decline in crude oil recovery.

Method used

The cavitation coupled electrochemical polarization process is used to modify the oil field return wastewater into nanobubbly jellyfish liquor and mixed with additional polyacrylamide to prepare nano-intelligent composite oil-repellent material. The material extends the polymer molecular chain through the interaction between the negative charge of nanobubble and the polymer molecular chain, improves the initial viscosity, and maintains the stability of viscosity through continuous oxidation and bactericidal effects.

Benefits of technology

It significantly improves the initial viscosity and viscosity retention rate of the polymer solution, extends the service life of the oil-fighting material, and improves the recovery rate of crude oil.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119823744A_ABST
    Figure CN119823744A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of new material technology and recovery efficiency improvement in oilfield development, and relates to a nano-composite oil displacement material as well as a preparation method and application thereof. According to the nano-composite oil displacement material provided by the invention, the nano-bubble jellyfish liquid is prepared by adopting a cavitation coupling electrochemical polarization process, and then the nano-bubble jellyfish liquid and the polymer are compounded to prepare a finished product; the nano-composite oil displacement material has multiple effects of high initial viscosity, low viscosity loss in a migration process, continuous oxidation of reducing substances in a stratum, continuous inhibition of bacterial growth, continuous improvement of stratum energy and the like, and has relatively high intelligence; the two oil displacement materials of the nano bubble jellyfish liquid and the polymer are organically fused and mutually promoted, the recovery efficiency improving effect is higher than that of the sum of oil increasing of a single oil displacement material, and the continuous oil increasing effect is remarkable; in the preparation process of the nanobubble jellyfish liquid, non-ideal components, such as oil and suspended solids, of an original system entering the stratum are reduced, and the nanobubble jellyfish liquid has remarkable benefits of protecting ecology.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of new material technology and oil field development to enhance recovery rate, and relates to a nano composite oil displacement material and a preparation method and application thereof. Background Art

[0002] Energy is the food of industry and the lifeblood of the national economy. In 2023, my country consumed nearly 700 million tons of crude oil, and its dependence on foreign crude oil exceeded 70%, far higher than the internationally recognized safety line of 50%. At present, my country's major oil fields are in the middle and late stages of development, and the main oil fields under development have entered the high water content period or the ultra-high water content period. The distribution of residual oil is very complex, and it is difficult to solve the existing stock technology. How to efficiently develop and improve the efficiency of residual oil recovery (enhanced oil recovery, EOR) requires scientific and technological innovation, and the residual oil should be exploited through effective technical means.

[0003] According to the different development methods used in different stages of oil field development, petroleum engineers call the self-flowing oil recovery stage primary oil recovery, the water injection development stage secondary oil recovery, and the mixed phase drive, chemical drive, thermal oil recovery and other stages to further improve the oil recovery effect tertiary oil recovery. Among them, chemical flooding is a process method that dissolves different chemicals into water and injects them into the reservoir in batches after the completion of secondary oil recovery, including polymer drive, alkali drive, surfactant drive, composite drive, foam drive, etc. Its basic principle is to increase the viscosity of the injected formation fluid and reduce the "binding" ability of the rock to crude oil, so as to achieve the purpose of improving the sweep efficiency and displacement efficiency.

[0004] Polymer flooding is a commonly used technical means in my country. Polymer flooding is to inject a certain type and amount of polyacrylamide into the water body. Polymer flooding technology has become an important technical means to maintain the sustained high production of major oil fields in my country and improve the level of oil field development in the later stage of high water content. With the continuous expansion of the industrial production scale of polymer flooding, especially after the oil fields enter the ultra-high water content period, the output of oily wastewater continues to increase, while the supply of low-mineralization clean water is becoming increasingly tight. The method of preparing and diluting polymer solutions with clean water not only wastes clean water resources, but also discharges a large amount of produced wastewater, seriously polluting the environment.

[0005] The mobility control of polymer solution is one of the important mechanisms of polymer flooding. For homogeneous oil layers, under normal water flooding conditions, the viscosity of injected water is often lower than that of crude oil, and the oil-water mobility ratio is unreasonable during the flooding process, resulting in a rapid increase in the water content in the produced fluid, and prematurely reaching the limit water content allowed by oil production economics. The actual oil recovery efficiency is far less than the limit oil recovery efficiency. The result of injecting polymer into the oil layer is that the oil-water mobility ratio in the flooding process is greatly improved.

[0006] Polymer solution has the effect of adjusting the profile. Polymer solution not only has the effect of adjusting the profile and expanding the swept volume, but also can improve the oil recovery efficiency. The mechanism of improving the oil recovery efficiency is manifested in the following aspects: (1) Bulk viscosity The polymer has resistance coefficient and residual resistance coefficient in the oil layer, which is the main reason for displacing the residual oil and clustered residual oil that are not affected by water flooding. The increase in bulk viscosity of the polymer solution, coupled with its elastic effect, improves the water-oil mobility ratio and the water flooding front, and can displace the residual oil and clustered residual oil that are not affected by water flooding; (2) The interfacial viscosity increases the viscosity of the polymer solution in the porous medium and is the main mechanism for displacing film-like and island-like residual oil; (3) The tensile viscosity makes the polymer solution viscoelastic, which is the main reason for displacing blind residual oil. Flexible polymer molecules will deform under stress, and their elasticity will cause them to recover and shrink. Therefore, when a flexible polymer solution with viscoelasticity passes through a porous medium, there is both shear flow and tensile flow. In particular, when the polymer molecules flow through the place where the pore size changes, the polymer molecules are stretched and show elasticity. This characteristic makes the polymer solution entering the blind end pore have a normal force perpendicular to the flow direction and pointing to the connected pores. It is under the action of the above-mentioned viscoelasticity of the polymer solution that the polymer solution can enter the blind end to displace oil and improve the recovery rate of crude oil.

[0007] In summary, the oil displacement of polymers depends on the bulk viscosity, interfacial viscosity and pull-up viscosity. It can be seen that how to ensure the viscosity of the prepared polymer aqueous solution and maintain the stability of the viscosity during use is of great significance.

[0008] At present, due to the limitation of clean water source and economic benefits, the polymer flooding in oil fields in my country generally adopts the scheme of "mixing sewage with sewage and diluting sewage", firstly preparing high-concentration polymer solution with sewage, and then diluting the high-concentration polymer solution with sewage. All major oil fields use sewage to prepare polymer flooding materials for sewage dilution. The initial viscosity of the polymer and the viscosity retention rate during operation are low, and there are two main defects: on the one hand, it increases the investment in polymer, and on the other hand, the effect of polymer flooding is difficult to guarantee.

[0009] The high mineralization of sewage, high content of reducing substances, and large number of microorganisms lead to low initial viscosity of the polymer solution prepared with sewage, large viscosity loss during operation, and continuous decline in crude oil recovery. Since the viscosity loss problem when preparing polymer solution with sewage has not been solved, sewage dilution has an adverse effect on the viscosity of the polymer solution and its oil recovery effect.

[0010] Commonly used sewage treatment technologies at home and abroad mainly include sedimentation (natural, coagulation, inclined plate, pressure sedimentation, etc.), coalescence, flotation (pressure dissolved air and mechanical induction), filtration (general mechanical filtration, walnut shell filtration, modified fiber ball bundle filtration), fine filtration (pleated filter element and ceramic filter rod microporous filtration), etc. In the future, it will develop towards high-efficiency sedimentation, jet suspension, fine filtration and membrane separation, electrophoresis, electroflocculation, electrosuspension, biological treatment and other directions.

[0011] The inventor's early research work disclosed a preparation device, preparation method and application of nano bubble oil recovery material (Chinese patent CN 118217834 A). A nano bubble oil recovery material was prepared by the nano bubble oil recovery material preparation device. The nano bubble oil recovery material is mainly used for water flooding secondary oil recovery, overcoming the problems of large water consumption, high energy consumption and high water content of produced fluid in the existing secondary oil recovery water flooding process.

[0012] In the research on sewage chemical treatment agents, the existing technology mainly focuses on the research and development of chemical agents, such as deoxidizers, bactericides, degreasers, flocculants, corrosion inhibitors and flocculants.

[0013] At present and in the future, we will focus on developing high-efficiency, multifunctional composite and environmentally friendly products, such as high-efficiency corrosion inhibitors for produced water and injected water, corrosion inhibitors for use under harsh conditions, non-phosphorus corrosion inhibitors, composite deoxidizers, low-foam or no-foam surfactant-type bactericides, microbial flocculants, biological demulsifiers, etc. Summary of the invention

[0014] The technical problem to be solved by the present invention is to solve the problem that the polymer solution prepared in the prior art has low initial viscosity and large viscosity loss during use. The core of the problem is that the material quality and performance of the prepared polymer are relatively low. The present invention further provides a nano-composite oil-displacing material and its preparation method and application.

[0015] The present invention starts from the source of polymer preparation of sewage, invents new technology and new process to prepare a new intelligent oil displacement material, realizes viscosity maintenance and oil increase of polymer solution, and improves crude oil recovery rate.

[0016] Invention idea: At present, the production of oilfield polymer solution adopts the "dirty-to-dirty dilution" process, which first uses sewage to prepare a high-concentration polymer solution, and then dilutes it with sewage, referred to as "dirty-to-dirty dilution". The polymer solution produced by this process has a low initial viscosity, a large viscosity loss during migration, and a rapid decrease in viscosity value, which is the fundamental reason for the continuous decline in crude oil recovery. The low initial viscosity of the polymer solution produced by the "dirty-to-dirty dilution" process is due to the influence of reducing substances and bacteria in sewage, and the large viscosity loss during migration is due to the presence of new reducing substances and bacteria in the formation.

[0017] The present invention uses a cavitation-coupled electrochemical polarization process to modify oilfield reinjection wastewater into an intelligent nano bubble water mother liquid material, and in the process fully oxidizes and reduces components to kill microorganisms and bacteria. Subsequently, the intelligent nano bubble water mother liquid is used to produce an oil displacement polymer solution. The nano composite oil displacement material provided by the present invention is a nano intelligent composite oil displacement material, and its intelligence is embodied in: (1) The nanobubble mother liquid contains a large number of nanobubbles. The nanobubbles contain a large amount of negative charges and are distributed in the bulk phase. The polymer contains negatively charged groups. The negative charges carried by the nanobubbles repel each other with the negative charges in the polymer, thereby intelligently promoting the extension of the polymer molecular chain, expanding the spatial volume of the polymer geometric conformation, further promoting the dissolution and diffusion of the polymer, and increasing the initial viscosity of the polymer solution. Furthermore, during the operation, the nanobubble mother liquid containing a large amount of oxygen, distributed in the bulk phase, and having negative charges can sustainably increase the dispersion and swelling of the polymer throughout the oil displacement process, promote the extension of the polymer molecular chain, and achieve the viscosity retention of the polymer solution.

[0018] (2) The nanobubble mother liquid contains a large number of nanobubbles, which contain a large amount of oxygen and ozone. Since the nanobubbles have the self-pressurization and contraction behavior, they can ensure the slow and continuous release of oxygen and ozone. During the oil recovery operation, they have a continuous oxidation and bactericidal effect, continuously oxidizing the reducing substances in the formation and inhibiting the growth of bacteria, thereby achieving the viscosity maintenance of the polymer solution.

[0019] (3) During the production operation, as mentioned above, the nanobubble water mother liquor containing a large amount of oxygen, distributed in the bulk phase, and having a negative charge can sustainably increase the dispersion and swelling of the polymer, promote the extension of the polymer molecular chain, and achieve the viscosity of the polymer solution, thereby improving the correlation between the polymer and the water in the formation, effectively slowing down the water stratification phenomenon, and efficiently maintaining the viscosity of the nano-intelligent composite oil recovery material during the production operation, ultimately achieving the goal of improving EOR.

[0020] (4) The nano intelligent composite oil-displacing material provided by the present invention is "small enough" to basically achieve full reservoir coverage; the nano intelligent composite oil-displacing material is "strongly hydrophobic and oleophilic", repels water and is attracted to oil, has self-driving force, and achieves intelligent oil finding, intelligent long-term profile adjustment, and unblocking; and further promotes "dispersed oil aggregation", can capture dispersed oil, form oil walls or oil-rich zones, and be driven out.

[0021] (5) A certain amount of active hydrogen is generated during the electrochemical polarization process. The active hydrogen exists in the mother liquor in the form of nanobubbles. Active hydrogen has the characteristics of small size and strong permeability. It can easily enter the cracks of rocks, destroy the interaction between oil and rock, and increase the probability of oil being driven out.

[0022] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows: The invention discloses a nano composite oil displacement material, which comprises nano bubble water mother liquid and polymer A; Wherein, the polymer A is an additionally added polyacrylamide; in the nanocomposite oil displacement material, the additionally added polyacrylamide has an addition concentration of 500-3000 ppm; The nano bubble water mother liquid is prepared by using oilfield reinjection wastewater as raw material through a cavitation-coupled electrochemical polarization process; The characteristic parameters of the nano bubble water mother solution are as follows: The diameter distribution range of the contained nanobubbles is 10 nm to 1000 nm; The concentration of nanobubbles contained is not less than 1.0×10 7 Pieces / mL; The pH value of the nanobubble water mother liquid is higher than the pH value of the oilfield reinjection wastewater by more than 0.25; The content of divalent iron is not higher than 1.0 mg / L; The divalent sulfur content is not higher than 2.0 mg / L; The sulfate-reducing bacteria content is not higher than 100 / mL; The content of saprophytic bacteria is not higher than 100 / mL; The iron bacteria content is not higher than 100 / mL.

[0023] Among them, the oilfield reinjection wastewater is oilfield wastewater, which generally refers to the wastewater separated from the produced liquid at the oilfield wellhead, and is transported to the polymer preparation station after production is completed at the oilfield wastewater station.

[0024] The original oilfield reinjection wastewater comes from the produced fluid of the oil well, which contains a trace amount of polyacrylamide. The preparation process of the nanobubble water mother liquid does not affect the polyacrylamide in the system, and the viscosity of the nanobubble water mother liquid is not higher than 1.2 mPa·s.

[0025] The main reason for the low viscosity of nanobubble water mother liquor is that the residual polyacrylamide fragments in the oilfield reinjection wastewater are affected by temperature and pressure when injected into the ground during the early chemical oil recovery, resulting in the breakage of polyacrylamide molecular chains and the formation of polyacrylamide fragments, which greatly reduce the molecular weight. The polyacrylamide fragments are too short to form intramolecular / intermolecular entanglement and agglomeration, resulting in a decrease in viscosity. Therefore, the original residual polyacrylamide in the oilfield reinjection wastewater has a small contribution to the viscosity and does not play a role in increasing the viscosity.

[0026] Furthermore, the viscosity of the nanocomposite oil displacement material is provided by the additionally added polyacrylamide, and the original residual polyacrylamide has no effect on viscosity.

[0027] In some embodiments, the nanocomposite oil displacement material further comprises other dilution water; the other dilution water is any one or a combination of oilfield reinjection wastewater and clean water; the volume ratio of the other dilution water to the nanobubble water mother liquid is 10%~90%:1.

[0028] In some embodiments, preferably, the nanocomposite oil displacement material further comprises other dilution water; the other dilution water is oilfield reinjection wastewater; the volume ratio of the other dilution water to the nanobubble water mother liquid is 40%~70%:1, and more preferably 40%~60%:1.

[0029] In some embodiments, the nanobubble water mother liquid is prepared by using oilfield reinjection wastewater as raw material through a cavitation coupled electrochemical polarization device to perform a cavitation coupled electrochemical polarization process; The cavitation-coupled electrochemical polarization device comprises a polarization tank, a polarization electrode, a raw material incoming pipeline, a raw material pump, a raw material inlet polarization tank pipe, a polarization controller, a polarization electrode control line, an ozone generator, an ozone delivery pipeline, a venturi drainage tube, a polarization liquid circulation pipeline, a circulation pump, a dirty oil overflow decontamination oil pipe port, a sampling and product collection port, a composite quantum dot material raw material tank, a plunger pump and a composite quantum dot material injection pipeline; in, A polarization electrode is arranged inside the polarization tank, the cathode of the polarization electrode is connected to the negative electrode of the polarization controller through a polarization electrode control line, and the anode of the polarization electrode is connected to the positive electrode of the polarization controller through a polarization electrode control line; The raw material incoming pipeline is connected to the raw material pump, and the raw material pump is connected to the raw material inlet polarization tank pipe through a connecting pipeline; the inlet end of the raw material inlet polarization tank pipe is located outside the polarization tank, and the outlet end is located at the bottom of the polarization tank; The inlet end of the venturi drainage tube is located outside the polarization tank, and the outlet end is located at the bottom of the polarization tank; the spray direction of the venturi drainage tube is from the inlet end to the outlet end; a reverse overflow facility is provided at the bottom of the polarization tank at the outlet end of the venturi drainage tube; The ozone generator is connected to the throat of the Venturi drainage tube through an ozone delivery pipeline to deliver air-ozone mixed gas; The composite quantum dot material raw material tank, the plunger pump, the composite quantum dot material injection pipeline, the polarization liquid circulation pipeline, and the inlet and outlet of the venturi drainage tube are connected in sequence; the composite quantum dot material injection pipeline is connected to the polarization liquid circulation pipeline; A dirty oil overflow and decontaminated oil pipe port is provided at the upper part of the side wall of the polarization tank; a sampling and product collection port is provided in the middle part of the side wall of the polarization tank; a circulating liquid outlet is provided at the lower part of the side wall of the polarization tank and is connected to a circulating pump through a pipeline, and the circulating pump is connected to the inlet of the Venturi drainage tube through a polarization liquid circulation pipeline.

[0030] Wherein, the venturi drainage tube is arranged in the polarization tank, the longitudinal center axis of the venturi drainage tube coincides with the longitudinal center axis of the polarization tank, the inlet end of the venturi drainage tube is located outside the polarization tank, and the outlet end is located at the bottom inside the polarization tank; the injection direction of the venturi drainage tube is from the inlet end to the outlet end; a reverse overflow facility is provided at the bottom of the polarization tank at the outlet end of the venturi drainage tube; wherein, the part of the venturi drainage tube located in the polarization tank and whose diameter gradually expands from top to bottom is the venturi injection expansion tube, and a reverse overflow facility is provided at the bottom of the polarization tank below the mixed fluid injection port of the venturi injection expansion tube for fluid reflux; the outlet end at the bottom of the venturi drainage tube is the mixed fluid injection port.

[0031] In some embodiments, the nanobubble water mother liquid is prepared by using oilfield reinjection wastewater as raw material through a cavitation coupled electrochemical polarization device to perform a cavitation coupled electrochemical polarization process, and the specific steps are as follows: The oilfield reinjection wastewater passes through the raw material pipeline and is pumped into the raw material inlet polarization tank pipe by the raw material pump until it enters the polarization tank; when the liquid level of the oilfield reinjection wastewater in the polarization tank reaches the sampling and product production outlet, the polarization controller is started to adjust the working voltage and working current to make the polarization electrode work, and the oilfield reinjection wastewater is electrode-polarized. After bubbles overflow from the surface of the polarization electrode, the circulation pump is started; the circulation pump circulates the oilfield reinjection wastewater in the polarization tank into the polarization liquid circulation pipeline until it reaches the inlet end of the Venturi drainage tube, and further sprays it into the polarization tank; after the circulation pump works stably, the ozone generator and the plunger pump are started respectively to pump the composite quantum dot material in the composite quantum dot material raw material tank. The wastewater is pumped into the inlet of the venturi drainage pipe by a plunger pump, and is further introduced into the polarization tank by spraying through the venturi drainage pipe. At the same time, when the circulating pump draws out the oilfield reinjection wastewater from the polarization tank and pumps it into the inlet end of the venturi drainage pipe and further sprays it into the polarization tank, a pressure difference is generated at the throat of the venturi drainage pipe, thereby introducing an air-ozone mixed gas. The cavitation process of the venturi drainage pipe forms an ozone fine bubble jet flow, which is sprayed out from the outlet end. The sprayed fluid overflows in the reverse direction through a reverse overflow facility at the bottom of the polarization tank at the outlet end of the venturi drainage pipe, flows through the polarization electrode for electrochemical polarization, and obtains a nano bubble water mother liquid after the cavitation-coupled electrochemical polarization process is completed.

[0032] Among them, the pressure difference generated at the throat of the Venturi drainage tube is 0.25~0.40MPa.

[0033] Among them, the Venturi cavitation process forms an ozone fine bubble jet flow, and the jet direction of the Venturi jet flow is from top to bottom to the bottom of the polarization tank. A reverse overflow facility is arranged at the bottom. The reverse overflow fluid passes through the working surface of the electrochemical polarization electrode. The ozone fine bubble jet flow undergoes an electrochemical reaction on the electrode surface. Part of the air-ozone mixture directly forms micro-nano bubbles during the cavitation process on the electrode surface, and part of the air-ozone mixture forms nano bubbles after cavitation on the electrode surface and then leaves the electrode.

[0034] The running time of the cavitation-coupled electrochemical polarization process is determined according to the product requirements of the nanobubble water mother solution.

[0035] Among them, the ozone generator uses purified air as the gas source, the purified air has a dew point lower than -50°C and a dust particle diameter less than 0.01 micron; the gas source of the ozone generator can be air as a direct gas source, or oxygen as a gas source, but using oxygen as a gas source is unsafe, and the present invention uses air as the gas source.

[0036] In some embodiments, the composite quantum dot material is a sulfur-doped carbon quantum dot material, with sulfur powder as the sulfur source and carboxymethyl cellulose as the carbon source. The sulfur powder and carboxymethyl cellulose are dispersed in an alkaline solution to obtain a dispersion, and then oxygen is introduced to heat the reaction, and then post-processed to obtain the sulfur-doped carbon quantum dot material; the amount of the composite quantum dot material added is based on the amount of oilfield reinjection wastewater treated, and the amount added is 2.5~7.5 mg / kg oilfield reinjection wastewater.

[0037] In some embodiments, preferably, the composite quantum dot material is a sulfur-doped carbon quantum dot material, with sulfur powder as the sulfur source and carboxymethyl cellulose as the carbon source, the sulfur powder and carboxymethyl cellulose are dispersed in an alkaline solution to obtain a dispersion, and then oxygen is introduced to heat the reaction, and then post-processed to obtain the sulfur-doped carbon quantum dot material; the amount of the composite quantum dot material added is based on the amount of oilfield reinjection wastewater treated, and the amount added is 2.5~5.0 mg / kg oilfield reinjection wastewater.

[0038] Among them, the sulfur-doped carbon quantum dot material is a polarization aid, the sulfur-doped carbon quantum dot material has anti-scaling and corrosion inhibition properties, protects the electrode and prolongs the service life of the electrode, and the average particle size of the sulfur-doped carbon quantum dot material is 2.5~3.0 nm.

[0039] The sulfur-doped carbon quantum dot material is diluted with clean water or product water sampled from the middle of the side wall of the polarization tank and the product outlet to obtain a sulfur-doped carbon quantum dot material solution; the sulfur-doped carbon quantum dot material solution is placed in a composite quantum dot material raw material tank and pumped into the polarization tank by a plunger pump. The mass content of the sulfur-doped carbon quantum dot material in the sulfur-doped carbon quantum dot material solution is 2% to 10%, preferably 5%. If not otherwise specified, a 5% mass content sulfur-doped carbon quantum dot material solution is used in the embodiment.

[0040] Specifically, preferably, the sulfur-doped carbon quantum dot material is prepared by the following method (for the specific experimental method, see Chinese patent CN 117603678 A), and the specific steps are: fully dispersing sublimated sulfur powder and carboxymethyl cellulose in an alkaline solution to obtain a dispersion, then introducing oxygen to heat the dispersion, and then post-treating the dispersion to obtain the sulfur-doped carbon quantum dot material; wherein the average particle size of the prepared sulfur-doped carbon quantum dot material is 2.5~3 nm.

[0041] Specifically, the sulfur-doped carbon quantum dot material emits blue fluorescence under 365 nm ultraviolet light excitation.

[0042] Specifically, the mass ratio of the sublimated sulfur powder to the carboxymethyl cellulose is (1.4-1.8):1.

[0043] Specifically, the alkaline solution is a sodium hydroxide solution; the concentration of the alkaline solution is 1.8-2.2 mol / L; and the pH of the obtained dispersion is 8.5-9.4.

[0044] Specifically, the pressure of the oxygen introduced is 0.1~0.12Mpa.

[0045] Specifically, the temperature of the heating reaction is 75-125° C., and the time of the heating reaction is 24-72 hours.

[0046] Specifically, the post-treatment comprises the following steps: a. the reaction solution obtained by the heating reaction is subjected to ultrasound and then centrifuged to obtain the supernatant; b. the solution after filtration and dialyzation is freeze-dried under vacuum to obtain the sulfur-doped carbon quantum dot material.

[0047] Specifically, the dialysis is performed at a cutoff of 300-1000Da for 12-36 hours; and the freeze-drying time is 24-72 hours.

[0048] In some embodiments, the cathode of the polarizable electrode (2) is made of titanium alloy; the anode of the polarizable electrode (2) has a base material of titanium alloy, the surface of the titanium alloy is chemically plated, and the coating is platinum or ruthenium-iridium alloy; the operating voltage is 3.0-48.0 V; the operating current is 1.0-150.0 A / m 3.

[0049] In some embodiments, preferably, the cathode of the polarizable electrode is made of titanium alloy; the anode of the polarizable electrode is made of titanium alloy, the titanium alloy surface is chemically plated, and the coating is platinum or ruthenium-iridium alloy; the operating voltage is 12-24 V; the operating current is 1.0-5.0 A / m 3 .

[0050] In some embodiments, the structure of the polarized electrode can be the same as that in Chinese patent CN118217834A, or a rod-shaped electrode can be selected.

[0051] In some embodiments, further, it can also be selected that: the cathode of the polarization electrode is a cylindrical titanium alloy wire mesh, the anode is a flat titanium alloy wire mesh formed by bending 90° with the midline of the short side as the fold line to form a right-angle bent titanium alloy wire mesh (the surface coating is platinum), the longitudinal midline of the Venturi drainage tube is used as the center line, and the edges of the fold lines of four right-angle bent titanium alloy wire meshes of the same specifications are evenly arranged close to the center line, and the distance between the edges of each fold line and the center line is the same, and the cathode of the polarization electrode is sleeved on the periphery of the four right-angle bent titanium alloy wire meshes, and the central axis of the cathode coincides with the longitudinal midline of the Venturi drainage tube. The specific top view shows Figure 6 Figure A. Preferably, in the embodiment of the present invention, the cathode material of the polarized electrode is a titanium alloy wire mesh with a mesh size of 4×6 mm, a cylindrical electrode, a height of 120 mm, and a diameter of 56 mm; the anode material is a titanium alloy wire mesh with a surface coating of platinum, a mesh size of 2×3 mm, a short side midline plane bent at 90°, a short side length of 26 mm, and a height of 110 mm, according to Figure 6 Arrange according to Figure A.

[0052] The fluid ejected from the outlet of the Venturi drainage tube overflows in the reverse direction through the reverse overflow facility. In order to increase the contact area between the fluid and the surface of the polarization electrode, any number of anode bent titanium alloy wire meshes with the same specifications and the same bending angles (surface coating is platinum) can be selected. The sum of the angles at the bending angles of any number of anode bent titanium alloy wire meshes with the same specifications is 360°. The edges where the fold lines of the bent titanium alloy wire meshes are located are evenly arranged close to the center line, and the distances between the edges where the fold lines are located and the center line are the same. The cathode of the polarization electrode is set on the periphery of any number of anode bent titanium alloy wire meshes, and the central axis of the cathode coincides with the longitudinal center line of the Venturi drainage tube. Specifically, Figure 6 Figure B.

[0053] In some embodiments, the gas source of the ozone generator (8) is air; the concentration of ozone in the air-ozone mixture is 5-30 mg / L; and the volume ratio of the air-ozone mixture to the oilfield reinjection wastewater in the polarization tank is 5%-20%:1.

[0054] In some embodiments, the gas source of the ozone generator (8) is air; the concentration of ozone in the air-ozone mixture is 10-20 mg / L; and the volume ratio of the air-ozone mixture to the oilfield reinjection wastewater in the polarization tank is 5%-20%:1.

[0055] In some embodiments, the nanocomposite oil displacement material has a viscosity retention rate of not less than 94.00% after 15 days of storage, not less than 90.00% after 30 days of storage, and not less than 75.00% after 90 days of storage in an airtight condition.

[0056] Furthermore, the present invention discloses a method for preparing the above-mentioned nanocomposite oil-displacing material, wherein the nanobubble water mother liquid and polymer A are mixed evenly to obtain the nanocomposite oil-displacing material; or, Mix other dilution water, nano bubble water mother liquid and polymer A to obtain nano composite oil displacement material; The other dilution water is any one of oilfield reinjection wastewater and clean water or a combination of the two.

[0057] Wherein, the polymer A is additionally added polyacrylamide; in the nano-composite oil displacement material, the additionally added polyacrylamide has an addition concentration of 500-3000 ppm.

[0058] Wherein, the nano bubble water mother liquid contains polyacrylamide, but it does not play a role in viscosity.

[0059] In some embodiments, preferably, in the method for preparing the nanocomposite oil displacement material, a portion of the nanobubble water mother liquid and the additionally added polymer A are mixed, and then mixed with the remaining nanobubble water mother liquid to obtain the nanocomposite oil displacement material; or, After mixing other dilution water and the additionally added polymer A, the mixture is mixed with the nano bubble water mother solution to obtain a nano composite oil displacement material; The other dilution water is any one of oilfield reinjection wastewater and clean water or a combination of the two.

[0060] The application of the above-mentioned nanocomposite oil displacement material in oil production is also within the protection scope of the present invention.

[0061] Specifically, the nanocomposite oil displacement material improves the oil recovery rate due to low viscosity loss.

[0062] Beneficial effects: (1) The process for preparing nanobubble water mother liquor of the present invention generates oxygen and nanobubbles during the electrode polarization process. Meanwhile, a large number of micro-nanobubbles are generated during the process of ozone entering the water body through the Venturi aeration device, thereby improving the efficiency of generating nanobubbles in the electrochemical process. Oxygen and ozone are wrapped in the nanobubbles, which continuously oxidize new reducing substances in the formation during the oil displacement migration process, inhibit the growth of bacteria in the formation, and intelligently maintain the viscosity of the oil displacement material.

[0063] (2) In the ozone fine bubble coupled electrochemical polarization process for preparing the nanobubble water mother liquid of the present invention, the electrochemical polarization process and the ozone fine bubble cooperate to break the emulsion, and the aeration process deeply breaks the emulsified oil remaining in the water body and blows it to the surface for recovery. The oil and suspended matter in the raw water are greatly reduced, reducing the damage of sewage to the formation. It can effectively reduce the non-ideal components such as oil and suspended matter in the original system that enter the formation, and has a significant benefit in protecting the ecology.

[0064] (3) The composite quantum dot material is used in the process of preparing the nano bubble water mother liquid of the present invention. The composite quantum dot material is a new green inorganic synthetic material. During use, the efficiency of electrochemical polarization reaction is improved, the electrode is scale-inhibited and corrosion-inhibited, and the electrode is protected. At the same time, it has sterilization efficiency and enhances the intelligence of the oil displacement material. At the same time, (1) the composite quantum dot material carries a negative charge, which repels the negative charge on the surface of the nano bubble, can increase the transfer speed of the bubble on the electrode surface, prevent the bubble from growing too much on the electrode surface, and form bubbles of non-ideal diameter; (2) the surface of the composite quantum dot material concentrates negative charges, which can prevent the formation of dirt on the electrode surface; (3) the composite quantum dot material carries a negative charge, which can also promote the swelling of polyacrylamide, further improving the initial viscosity of the nano intelligent composite oil displacement material.

[0065] (4) In the process of preparing nanobubble water mother liquid by coupling ozone microbubble jet flow with electrochemical polarization, multiple mechanisms synergistically increase the initial viscosity of the nano-intelligent composite oil displacement material: (i) Ozone has strong oxidizing and bactericidal properties. After cavitation to form fine bubbles, the oxidizing and bactericidal properties are further enhanced. Strongly oxidizing atomic oxygen and strongly oxidizing hydroxyl radicals generated by ozone on the electrode surface are generated. Various strong oxidizing substances deeply oxidize reducing substances and kill bacteria. The reducing substances and bacteria that affect the viscosity of the polymer in the oilfield reinjection wastewater are deeply treated, the pH value of the nanobubble water mother liquor is increased, the Zeta potential of the nanobubble water mother liquor is greatly reduced, the oil content and suspended matter content are reduced, and other positive factors lead to an increase in the initial viscosity of the polymer solution.

[0066] (ii) Nanobubbles are generated during the electrochemical polarization process, and the oilfield reinjection wastewater is modified into a bulk nanobubble water mother liquor. The nanobubbles are negatively charged and are distributed in the mother liquor. The polymer molecules (polyacrylamide) contain negatively charged CN- With COOH - The negative charge of the nanobubble and the negative charge of the polymer molecule repel each other, accelerating the swelling and dispersion of the polymer in the nanobubble mother liquid until the potential of the entire solution system is balanced. This function is intelligent. The prepared nano intelligent composite oil-displacing material not only increases the initial viscosity, but also has a high degree of uniformity and stability.

[0067] (5) The present invention compounds nano bubble water mother liquid with polymer (such as polyacrylamide) to obtain a nano intelligent composite oil displacement material. The nano intelligent composite oil displacement material has the characteristics of high initial viscosity, low viscosity loss during migration, continuous oxidation of reducing substances in the formation, and inhibition of bacterial growth. Nano bubble water mother liquid and polyacrylamide synergistically drive oil to form a new oil displacement system to improve crude oil recovery. The oil displacement efficiency of the two has a synergistic effect, and the oil increase effect is higher than the sum of the oil increase of a single oil displacement material.

[0068] (6) When the nano intelligent composite oil-displacing material provided by the present invention is used, its performance can not only improve the initial viscosity of the polymer solution, but also reduce the viscosity loss during the migration process throughout the whole cycle, thereby achieving viscosity maintenance and oil increase; the nano bubbles in the nano intelligent composite oil-displacing material can increase the formation energy for a long time after entering the formation, and have a significant effect on continuous oil increase.

[0069] (7) Technological innovation leads. This invention realizes comprehensive innovation in existing polymer flooding technology, adopts physical processes to solve chemical problems, adopts new processes to prepare new materials, and systematically solves problems from the most basic raw materials. The integration of nanotechnology and enhanced oil recovery (EOR) technology can solve problems that traditional EOR technology cannot or is difficult to solve, such as low sweep efficiency, high cost, poor adaptability to harsh environments, and potential reservoir damage.

[0070] (8) The experimental test results of the nano-intelligent composite oil-displacing material provided by the present invention show that the nano-intelligent composite oil-displacing material has a high viscosity retention rate. Under air-tight conditions, the viscosity retention rate of the nano-intelligent composite oil-displacing material after 15 days of storage is not less than 94.00%, the viscosity retention rate after 30 days of storage is not less than 90.00%, and the viscosity retention rate after 90 days of storage is not less than 75.00%.

[0071] (9) The nano intelligent composite oil-displacing material provided by the present invention is "small enough" to basically achieve full reservoir coverage; the nano intelligent composite oil-displacing material is "strongly hydrophobic and oleophilic", repels water and is attracted to oil, has self-driving force, and achieves intelligent oil finding, intelligent long-term profile adjustment, and unblocking; it further promotes "dispersed oil aggregation", can capture dispersed oil, form oil walls or oil-rich zones, and be driven out.

[0072] (10) The nano intelligent composite oil displacement material provided by the present invention achieves oil increase through multiple mechanisms. While maintaining viscosity and increasing oil, the nano bubble water mother liquid itself has oil increase efficiency. The nano bubble water mother liquid and the polymer oil increase efficiency are highly integrated and superimposed to form a new intelligent oil displacement system, producing an effect of 1+1 greater than 2.

[0073] (11) Compared with the oil recovery efficiency of existing polymer solutions under the same operating conditions, the absolute oil recovery efficiency increased by more than 0.5%, and the relative oil recovery efficiency increased by more than 25%.

[0074] (12) The ozone fine bubble coupled electrochemical polarization technology provided by the present invention has strong adaptability and can be used for ordinary oily wastewater, deep-treated oily wastewater, and polymer-containing and oily wastewater. The produced water from the oil field can be recycled as water for the preparation of polymer solution, which has the effect of increasing viscosity and maintaining viscosity, and finally achieves the ultimate goal of increasing oil. The technical solution provided by the present invention can not only achieve the purpose of reducing investment and improving development effects, but also is an important way to ensure the sustainable development of oil fields, reduce environmental pollution, and improve economic benefits.

[0075] (13) The purpose of the present invention is to improve the correlation between polymer and oil. The main factors are viscosity index: 1. Initial value of viscosity; 2. Retention rate of polymer solution. The present invention uses nanobubble water mother liquid to compound with polymer. The nanobubble contains a large amount of negative charge, which is distributed in the bulk phase. The charge is evenly distributed. The negative charge and the negative charge on the polymer repel each other. The clustered negative charge of the nanobubble increases the repulsive force with the polymer, which can fully stretch the polymer molecules and increase the dissolution and diffusion of the polymer, thereby improving the viscosity of the polymer (the apparent viscosity can only be displayed after the polymer molecules stretch). At the same time, in the subsequent oil displacement operation process, the nanobubbles in the nano-intelligent composite oil displacement material can make the polymer further fully swell, realize the viscosity retention of the nano-intelligent composite oil displacement material, improve the correlation between polymer and oil, reduce the amount of polymer, reduce energy consumption, and improve EOR. BRIEF DESCRIPTION OF THE DRAWINGS

[0076] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments, and the above and / or other advantages of the present invention will become more clear.

[0077] Figure 1 A diagram of a cavitation-coupled electrochemical polarization device used to prepare nanobubble water mother solution in an embodiment of the present invention.

[0078] Figure 2 This is a comparison of the appearance of oilfield reinjection wastewater before and after polarization treatment.

[0079] Figure 3Laser scattering microscopy images of electrophoresis and Brownian motion video analysis of nanobubble water mother liquor obtained after polarization treatment of oilfield reinjection wastewater.

[0080] Figure 4 This is a dynamic change curve of the nanobubble water mother liquid injected into the physical simulation displacement experiment No. 1 of the nanobubble water mother liquid.

[0081] Figure 5 This is a dynamic change curve of the nanobubble water mother liquid injected into the physical simulation displacement experiment No. 2 of the nanobubble water mother liquid.

[0082] Figure 6 Diagram showing the arrangement of the cathode and anode of the polarized electrodes. DETAILED DESCRIPTION

[0083] The present invention can be better understood according to the following examples. However, it is easy for those skilled in the art to understand that the contents described in the examples are only used to illustrate the present invention, and should not and will not limit the present invention described in detail in the claims.

[0084] The experimental methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials described are commercially available unless otherwise specified.

[0085] 1. The general requirements for device preparation, startup, operation, and testing in the embodiment of the present invention are as follows: (1) Preparation of cavitation-coupled electrochemical polarization device for preparing nanobubble water mother solution: Figure 1 As shown, it mainly includes a polarization tank 1, a polarization electrode 2, a raw material incoming pipeline 3, a raw material pump 4, a raw material inlet pipe 5 for the polarization tank, a polarization controller 6, a polarization electrode control line 7, an ozone generator 8, an ozone delivery pipeline 9, a venturi drainage tube 10, a polarization liquid circulation pipeline 11, a circulation pump 12, a dirty oil overflow and dirty oil removal pipe port 13, a sampling and product production port 14, a composite quantum dot material raw material tank 15, a plunger pump 16 and a composite quantum dot material injection pipeline 17.

[0086] Among them, a polarization electrode 2 is arranged inside the polarization tank 1, the cathode of the polarization electrode 2 is connected to the negative electrode of the polarization controller 6 through the polarization electrode control line 7, and the anode of the polarization electrode 2 is connected to the positive electrode of the polarization controller 6 through the polarization electrode control line 7.

[0087] Among them, the raw material incoming pipeline 3 is connected to the raw material pump 4, and the raw material pump 4 is connected to the raw material inlet pipe 5 of the polarization tank through a connecting pipe; the inlet end of the raw material inlet pipe 5 of the polarization tank is located outside the polarization tank 1, and the outlet end is located at the bottom inside the polarization tank 1; the oilfield reinjection wastewater is pumped into the polarization tank 1 through the raw material pump 4.

[0088] Wherein, the venturi drainage tube 10 is arranged in the polarization tank 1, the longitudinal center axis of the venturi drainage tube 10 coincides with the longitudinal center axis of the polarization tank 1, the inlet end of the venturi drainage tube 10 is located outside the polarization tank 1, and the outlet end is located at the bottom inside the polarization tank 1; the injection direction of the venturi drainage tube 10 is from the inlet end to the outlet end; a reverse overflow facility is provided at the bottom of the polarization tank 1 at the outlet end of the venturi drainage tube 10; wherein, the venturi drainage tube 10 is located in the polarization tank 1 and the part whose diameter gradually expands from top to bottom is the venturi injection expansion tube, and a reverse overflow facility is provided at the bottom of the polarization tank 1 below the mixed fluid injection port of the venturi injection expansion tube for fluid reflux; the outlet end at the bottom of the venturi drainage tube 10 is the mixed fluid injection port.

[0089] Among them, the ozone generator 8 is connected to the throat of the Venturi drainage tube 10 through the ozone delivery pipeline 9, and is used to transport the air-ozone mixture; the ozone generator 8 uses purified air as the gas source, the ozone generator 8 adjusts the air volume and the ozone generation amount, and the air and ozone mixture is connected to the throat of the Venturi drainage tube 10 through the ozone delivery pipeline 9, and is used to transport the air and ozone mixture.

[0090] The composite quantum dot material raw material tank 15, the plunger pump 16, the composite quantum dot material injection pipeline 17, the polarization liquid circulation pipeline 11, and the inlet and outlet of the venturi drainage tube 10 are connected in sequence; the composite quantum dot material injection pipeline 17 is connected to the polarization liquid circulation pipeline 11. The plunger pump 16 pumps the composite quantum dot material in the composite quantum dot material raw material tank 15 into the polarization tank 1.

[0091] Among them, a dirty oil overflow and decontamination oil pipe port 13 is provided on the upper part of the side wall of the polarization tank 1 for discharging the dirty oil; a sampling and product production port 14 is provided in the middle part of the side wall of the polarization tank 1 for product sampling and production; a circulating liquid outlet is provided on the lower part of the side wall of the polarization tank 1, which is connected to a circulating pump 12 through a pipeline, and the circulating pump 12 is connected to the inlet of the venturi drainage pipe 10 through a polarization liquid circulation pipeline 11; the circulating pump 12 pumps the oilfield reinjection sewage into the inlet end of the venturi drainage pipe 10, and further sprays it into the polarization tank 1, so that a pressure difference is generated at the throat of the venturi drainage pipe 10, and then the air ozone mixture is introduced.

[0092] The effective capacity of the polarization tank 1 is preferably 30 L in the embodiment of the present invention (the expansion or reduction of the scale can be adjusted according to the actual industrial production scale).

[0093] The cathode material of the polarized electrode 2 used in the embodiment of the present invention is titanium alloy, the anode substrate of the polarized electrode 2 is titanium alloy, and the surface coating is platinum. The structure of the polarized electrode 2 can be the same as that in Chinese patent CN118217834A, and a rod-shaped electrode can also be selected.

[0094] Furthermore, it is also possible to choose: the cathode of the polarization electrode 2 is a cylindrical titanium alloy wire mesh, the anode is a flat titanium alloy wire mesh formed by bending 90° with the midline of the short side as the fold line to form a right-angle bent titanium alloy wire mesh (the surface coating is platinum), with the longitudinal midline of the Venturi drainage tube 10 as the center line, and the edges of the fold lines of four right-angle bent titanium alloy wire meshes of the same specifications are evenly arranged close to the center line, and the distance between the edges of each fold line and the center line is the same, and the cathode of the polarization electrode 2 is sleeved on the periphery of the four right-angle bent titanium alloy wire meshes, and the central axis of the cathode coincides with the longitudinal midline of the Venturi drainage tube 10. The specific top view shows Figure 6 Figure A. Preferably, in the embodiment of the present invention, the cathode material of the polarized electrode 2 is a titanium alloy wire mesh with a mesh size of 4×6 mm, a cylindrical electrode, a height of 120 mm, and a diameter of 56 mm; the anode material is a titanium alloy wire mesh with a surface coating of platinum, a mesh size of 2×3 mm, a short side midline plane bent at 90°, a short side length of 26 mm, and a height of 110 mm, according to Figure 6 Arrange according to Figure A.

[0095] The fluid ejected from the outlet end of the Venturi drainage tube 10 overflows in the reverse direction through the reverse overflow facility. In order to increase the contact area between the fluid and the surface of the polarized electrode, any number of anode bent titanium alloy wire meshes with the same specifications and the same bending angles (surface coating is platinum) can be selected. The sum of the angles at the bending angles of any number of anode bent titanium alloy wire meshes with the same specifications is 360°. The edges where the fold lines of the bent titanium alloy wire meshes are located are evenly arranged close to the center line, and the distances between the edges where the fold lines are located and the center line are the same. The cathode of the polarized electrode 2 is sleeved on the periphery of any number of anode bent titanium alloy wire meshes, and the central axis of the cathode coincides with the longitudinal center line of the Venturi drainage tube 10. Specifically, Figure 6 Figure B.

[0096] The ozone generator 8 uses purified air as a gas source, and the purified air has a dew point lower than -50°C and a dust particle diameter less than 0.01 micrometer. Note: The ozone generator in this application can use air as a direct gas source or oxygen as a gas source, but oxygen is unsafe, so this application uses air as a gas source.

[0097] The composite quantum dot material used in the embodiment of the present invention is a sulfur-doped carbon quantum dot material. The specific preparation method is detailed in Example 1 (i.e., preparation of multifunctional cellulose-based sulfur quantum dots) in paragraphs

[0025] -

[0032] of the specification of Chinese patent CN 117603678 A.

[0098] (2) The nanobubble water mother liquid is prepared by using oilfield reinjection wastewater as raw material through a cavitation coupled electrochemical polarization device to perform a cavitation coupled electrochemical polarization process. The specific steps are as follows: The oilfield reinjection wastewater passes through the raw material incoming pipeline 3 and is pumped into the raw material inlet polarization tank pipe 5 by the raw material pump 4 until it enters the polarization tank 1; when the liquid level of the oilfield reinjection wastewater in the polarization tank 1 reaches the sampling and product production outlet 14, the polarization controller 6 is started to adjust the working voltage and working current, so that the polarization electrode 2 works, and the oilfield reinjection wastewater is electrode-polarized. After bubbles overflow from the surface of the polarization electrode 2, the circulation pump 12 is started; the circulation pump 12 circulates the oilfield reinjection wastewater in the polarization tank 1 into the polarization liquid circulation pipeline 11 until it reaches the inlet end of the venturi drainage tube 10, and further sprays it into the polarization tank 1; after the circulation pump 12 works stably, the ozone generator 8 and the plunger pump 16 are started respectively to inject the composite quantum dot material in the composite quantum dot material raw material tank 15. The point material is pumped into the inlet of the venturi drainage tube 10 by the plunger pump 16, and is further introduced into the polarization tank 1 through the injection of the venturi drainage tube 10; at the same time, when the circulating pump 12 draws out the oilfield reinjection sewage from the polarization tank 1 and pumps it into the inlet end of the venturi drainage tube 10, and further injects it into the polarization tank 1, a pressure difference is generated at the throat of the venturi drainage tube 10, and then the air-ozone mixture is introduced. The cavitation process of the venturi drainage tube 10 forms an ozone fine bubble jet flow, which is ejected from the outlet end. The ejected fluid overflows reversely through the reverse overflow facility at the bottom of the polarization tank 1 at the outlet end of the venturi drainage tube 10, flows through the polarization electrode 2 for electrochemical polarization, and after the cavitation coupled electrochemical polarization process is completed, a nano bubble water mother liquid is obtained.

[0099] (3) Steps for starting up the device for preparing nanobubble water mother liquid: first start the raw material pump, start the polarization system after the liquid level in the polarization tank reaches the sampling and product collection port 14, adjust the working current and working voltage of the polarization system, observe whether there are bubbles overflowing from the electrode surface, and start the circulation pump 12 after judging that the polarization system is operating normally. After checking that the injection system is operating stably, start the ozone generator 8 and the plunger pump 16, and the whole system is started up.

[0100] (4) Operation of the device for preparing nanobubble water mother liquid: During the operation of the device, the operating time (the operating time is determined according to the characteristic parameters of the nanobubble water mother liquid product), operating current, operating voltage, air flow, ozone generation, venturi ejector flow rate and cumulative flow, and the total amount of dirty oil flowing out of the overflow and decontamination oil pipe outlet on the top of the polarization tank are monitored and recorded.

[0101] (5) Operating principle of the device: Venturi cavitation mechanism produces ozone micro-nano bubbles, polarization produces micro-nano bubbles, and redox reaction principle.

[0102] 2. Physical and chemical indicators and analysis methods of oilfield reinjection wastewater and nanobubble water mother liquor (1) Appearance: Oilfield water analysis method, standard number: SY / T 5523-2016.

[0103] (2) Odor: Oilfield water analysis method, standard number: SY / T 5523-2016.

[0104] (3) Density (g / cm 3 ): Oilfield water analysis method, standard number: SY / T 5523-2016.

[0105] (4) Viscosity (mPa·s): Viscosity measurement method, standard number: GB / T 10248-2008.

[0106] (5) pH value: Oilfield water analysis method, standard number: SY / T 5523-2016.

[0107] (6) Electrical conductivity (μs / cm): Oilfield water analysis method, standard number: SY / T 5523-2016.

[0108] (7) Total mineralization (mg / L): Oilfield water analysis method, standard number: SY / T 5523-2016.

[0109] (8) Oil content in water (mg / L): Technical requirements and analysis methods for water quality indicators for injection into clastic reservoirs, standard number: SY / T 5329-2022.

[0110] (9) Suspended matter (mg / L): Technical requirements and analysis methods for water quality indicators for injection into clastic oil reservoirs, standard number: SY / T5329-2022.

[0111] (10) Polymer concentration (mg / L): Polymer produced liquid test method, standard number: Q / SY DQ0928-2017.

[0112] (11) Total iron (mg / L): Technical requirements and analysis methods for water quality indicators for injection into clastic oil reservoirs, standard number: SY / T5329-2022.

[0113] (12) Fe 2+ (mg / L): Fink's reagent test method.

[0114] (13) S 2- (mg / L): Fink's reagent test method.

[0115] (14) Sulfate-reducing bacteria (cells / mL): bacterial culture test method.

[0116] (15) Saprophytic bacteria (number / mL): bacterial culture test method.

[0117] (16) Iron bacteria (counts / mL): bacterial culture test method.

[0118] (17) Zeta potential (mv): visual electrophoresis method, standard number: ISO13321.

[0119] (18) Nanobubble particle concentration (particles / mL): Nanoparticle tracking and counting method.

[0120] (19) Particle size distribution: nanoparticle tracking method.

[0121] 3. Comparison of physical and chemical indicators between nano bubble water mother liquor and oilfield reinjection wastewater Compare indicators such as pH value, Zeta potential, divalent iron content, divalent sulfur content, sulfate-reducing bacteria, saprophytic bacteria content, and iron bacteria content.

[0122] 4. The physical and chemical indicators and analysis methods of polymer solutions prepared from general sewage and nano-intelligent composite oil recovery materials were evaluated through parameters such as viscosity (mPa·s), viscosity retention rate (%), and oil recovery efficiency (%).

[0123] 5. The data in the embodiment of the present invention is detected by the relevant oil production plant of Daqing Oilfield Co., Ltd.

[0124] 6. The source of water used in the embodiment of the present invention (i.e., the source of the raw water described below): water from the polymer preparation station of the first oil production plant of Daqing Oilfield Co., Ltd., the sewage pipe diameter is 500 mm, and the daily sewage throughput is about 20,000 cubic meters. Since the sewage is in a flowing state and comes from different batches of sewage, the physical and chemical indicators of the samples at the same sampling point in the sewage pipe vary greatly, including oil content, suspended matter, conductivity, bacteria, metal ions and other parameters. (Note: No additional agents were added to the raw sewage used in the experiment, and no treatment process including oxygen exposure was performed).

[0125] Example 1: Preparation of Nanobubble Water Stock Solution and Characterization of Physical and Chemical Properties (1) Preparation of nanobubble water mother liquid 30 L of raw water was collected, and at the same time, samples were taken from sterile bottles for analysis of physical and chemical indicators. The nanobubble water mother liquor was prepared according to the above-mentioned general device start-up and shutdown specifications, and samples were taken for testing. Among them, in the embodiment of the present invention, the cathode material of the polarization electrode 2 in the cavitation-coupled electrochemical polarization device is a titanium alloy wire mesh with a mesh specification of 4×6 mm, a cylindrical electrode, a height of 120 mm, and a diameter of 56 mm; the anode material is a titanium alloy wire mesh with a surface coating of platinum, a mesh specification of 2×3 mm, a 90° bend in the midline plane of the short side, a short side length of 26 mm, and a height of 110 mm, according to Figure 6 Arrange according to Figure A.

[0126] The operating process conditions are shown in Table 1, and the experimental results are compared in Table 2.

[0127]

[0128]

[0129] From Table 2, we can see that: (i) After the oilfield reinjection wastewater (raw water) was treated with polarized water, the pH value increased, and the total mineralization did not change significantly, which indicates that in the water treatment process, in addition to electrode polarization and ozone action, no other inorganic compounds were introduced. (ii) After the oilfield reinjection wastewater was treated with polarized water, the polymer concentration showed a slight downward trend, but the overall change was not obvious; the oil content and suspended matter showed a significant downward trend; divalent iron and reduced sulfide showed a relatively obvious downward trend; the bacterial content in the water showed an extremely obvious decline, and the longer the treatment time, the more obvious the decline in reduced substances and bacteria. (iii) The Zeta potential in Table 2 became more negative, indicating that the electronegativity of the product nanobubble water mother liquor increased; the pH increased by 0.5, indicating that the alkalinity of the product nanobubble water mother liquor increased.

[0130] Comparison of the appearance of oilfield reinjection wastewater before and after polarization treatment Figure 2 As shown in the figure, a is the appearance of oilfield reinjection wastewater (raw water) before polarization, and b is the appearance of nanobubble water mother liquor obtained after polarization of oilfield reinjection wastewater for 75 minutes. It can be seen from the figure that after polarization treatment, the oil content and suspension in the wastewater are significantly reduced, and the transmittance is significantly increased. Electrophoresis and Brownian motion video analysis laser scattering microscope images of nanobubble water mother liquor obtained after polarization treatment of oilfield reinjection wastewater are shown in Figure 3 As shown in the figure, it can be seen that there are a large number of nanobubbles in the nanobubble mother liquid.

[0131] Example 2: Advantages of the sewage modification solution provided by the present invention The treatment process of the present invention mainly involves ozone microbubbles formed by electrochemical polarization coupled cavitation. In order to further clarify the mutual promotion mechanism of the two effects of the present invention, the following experiments were designed using the control variable method: 1. Polarization treatment group: electrochemical polarization treatment alone; 2. Ozone treatment group: ozone microbubble jet flow treatment alone; 3. Polarization + ozone treatment group: electrochemical polarization treatment coupled with ozone microbubble jet flow treatment. The control group was raw water sewage.

[0132] 30 L of raw water was resampled, and the sampling point was the same as that in Example 1. The experimental operation process was the same as that in Example 1. The experimental operation parameters of the polarization + ozone treatment group are shown in Table 3. The nanobubble water mother liquor obtained by polarization for 45 min was subjected to routine testing, and the experimental results are shown in Table 4. There was no current in the polarization treatment group, and there was no ozone in the electrochemical polarization treatment alone. Note: In the table, SRB is sulfate-reducing bacteria; FB is iron bacteria; TGB is saprophytic bacteria. Among them, in the embodiment of the present invention, the cathode material of the polarization electrode 2 in the cavitation-coupled electrochemical polarization device is titanium alloy wire mesh, with a mesh specification of 4×6 mm, a cylindrical electrode, a height of 120 mm, and a diameter of 56 mm; the anode material is titanium alloy wire mesh, the surface coating is platinum, the mesh specification is 2×3 mm, the short side midline plane is bent at 60°, the short side length is 26 mm, and the height is 110 mm, according to Figure 6 Arrange according to Figure B, n=6.

[0133]

[0134]

[0135] It can be seen from the experimental data in Table 4 that among the three different treatment conditions, the effect of electrochemical polarization treatment coupled with ozone fine bubble jet flow treatment is the best, in which the oil and suspended solids in the sewage are reduced by one order of magnitude; the number of bacteria is reduced by at least four orders of magnitude; the total iron, divalent iron, and reduced sulfide content are reduced by more than 50%; the polymer concentration also shows a certain downward trend, which shows that there is a synergistic effect between the two technical points of electrode polarization and ozone injection, and the optimal treatment effect can be achieved when they exist at the same time. Under single electrode polarization / single ozone treatment, the treatment effects of the two are roughly similar, but the removal of reducing substances and bacteria by pumping ozone is better than that of simply applying electrodes.

[0136] The above results show that the coupling of electrochemical polarization and ozone micro-bubble jet provided by the present invention enhances the effectiveness of single polarization and single ozone, respectively. The hydroxyl radicals generated by electrochemical polarization in an ozone atmosphere increase, thereby having a stronger oxidizing effect on reducing substances in water bodies and a more significant removal ability for bacteria in water.

[0137] Example 3: Nanobubble water mother liquid independent increase in recovery performance experiment (1) 30 L of sample was taken again. The raw water collection point was the same as that in Example 1. The preparation quantity, experimental process, and electrodes were the same as those in Example 1. The adjusted preparation process parameters are shown in Table 5. The physical and chemical properties analysis data of the raw water and nanobubble water mother liquor are shown in Table 6.

[0138]

[0139]

[0140] Comparing Table 2 and Table 6, the physical and chemical indicators of the raw water on site vary greatly. Judging from the appearance, the raw water of Example 3 is of poor quality. The operating process parameters such as ozone supply, air supply, and current intensity are adjusted, and the coupling time is 40 minutes. From the experimental data in Table 6, it can be seen that the quality of the nanobubble water mother liquor product is stable.

[0141] (2) Conducting nanobubble water mother liquid oil displacement test: pressure change test, the experimental core is an artificial core with different effective permeabilities. First, sewage is used for water displacement. After sufficient water displacement until the produced fluid is completely oil-free, nanobubble water mother liquid is used for displacement. The injection volume of nanobubble water mother liquid displacement is 0.50 PV. Then sewage is used for subsequent water displacement. The pressure change data of nanobubble water mother liquid entering the core is shown in Table 7.

[0142]

[0143] Table 7 shows the test results of pressure changes at different effective permeabilities. After the injection of nanobubble water mother liquid, the pressure is significantly increased compared with the water flooding process. Compared with the high permeability core, the pressure increase of the low permeability core is higher. As the core permeability decreases, the resistance coefficient and the residual resistance coefficient both show an upward trend, which shows that the nanobubble water mother liquid has a stronger plugging effect on the low permeability oil layer.

[0144] (3) Physical simulation experiment of raw wastewater and nanobubble water mother liquor The oil displacement experiment was carried out using a three-layer heterogeneous core of 4.5*4.5*30 cm. First, sewage was used for water displacement. After sufficient water displacement until the produced fluid was completely oil-free, nanobubble water mother liquid was used for displacement. The injection volume of nanobubble water mother liquid displacement was 0.75PV. Then sewage was used for subsequent water displacement. The experimental pressure and the produced fluid were observed and recorded at regular intervals during the experiment. The permeability of the core used in this experiment is very representative in my country, and repeatable experiments were carried out using such cores.

[0145] from Figure 4 , Figure 5 , Table 8 Analysis of pressure changes during the test process, from Figure 4 , Figure 5 The analysis of the water content of the produced fluid shown in Figure 1 and the analysis of the pressure change in the oil displacement experiment in Table 8 show that the pressure increased and fluctuated during the injection of the nanobubble water mother liquid, with the maximum pressure increase of about 1.5 times, and the maximum reduction of the water content of the produced fluid was close to 95%. From the results of the physical simulation experiment in Table 9, based on the sewage displacement limit, the injection of 0.75PV nanobubble water can increase the recovery factor by 2.79 percentage points, and the produced fluid did not emulsify.

[0146]

[0147]

[0148] The results of Example 3 show that the nanobubble water mother liquid provided by the present invention has the performance of improving crude oil recovery, and the relative recovery rate of 0.75PV injection volume increases by 2.79%.

[0149] Example 4: Experiment on viscosity enhancement and viscosity maintenance of nano-intelligent composite oil displacement materials The nanobubble water mother solution obtained in Example 3 was used to prepare and dilute the polymer solution.

[0150] The polymer is a product of Daqing Refining and Chemical Company of China National Petroleum Corporation, polyacrylamide dry powder, Mw=25 million, and effective content 89.4%.

[0151] The "dirty-mixing-dirty-dilution method" was adopted to prepare the polymer mother liquor of 5000 mg / L by first mixing the sewage with the polymer. (1) Oilfield reinjection sewage group: The polymer mother liquor was diluted to 1800 mg / L with the oilfield reinjection sewage (the raw water was collected again, and the collection point was the same as that in Example 1) to obtain the polymer solution diluted with the oilfield reinjection sewage. (2) Nanobubble water mother liquor group: The polymer mother liquor was diluted to 1800 mg / L with the nanobubble water mother liquor to obtain the nanobubble water mother liquor diluted polymer solution (i.e., nano-intelligent composite oil displacement material). Among them, the oilfield reinjection sewage needs to be filtered with filter paper before use.

[0152] Viscosity test: Use a shearing instrument to shear for 1 minute and 40 seconds, and measure the viscosity of the polymer solution diluted with oilfield reinjection wastewater and the polymer solution diluted with nanobubble water mother liquid at a water bath temperature of 45°C. At the same time, seal the samples with oxygen, and then use the same method to test their viscosity and calculate the viscosity retention rate on the 3rd, 7th, 15th, 30th, 60th, and 90th days, and evaluate the viscosity stability based on the viscosity retention rate. Note: Multiple samples of each group are prepared in parallel.

[0153]

[0154] The experimental results are shown in Table 10. The initial viscosity and viscosity retention rate of the polymer solution prepared by the nanobubble water mother liquor group are much higher than those of the oilfield reinjection wastewater group, and the retention rate still reaches 79.30% after 90 days.

[0155] Example 5: Comparison of oil recovery by wastewater injection and nano-intelligent composite oil recovery materials Experimental polymer solution: The polymer solution diluted with the oilfield reinjection wastewater obtained in Example 4 and the polymer solution diluted with nano bubble water mother liquid (ie, nano intelligent composite oil displacement material) were used to carry out oil displacement experiments.

[0156] Experimental materials: two artificial cores A and B, with specifications of 30 cm×4.5 cm×4.5 cm, the gas permeability of core A is 1100 mD, and the gas permeability of core B is 1180 mD, both of which are Class II cores.

[0157] Experimental oil: simulated oil prepared from the combined station’s exported crude oil and aviation kerosene. Its viscosity was measured by a Brookfield viscometer at a water bath temperature of 45°C to be 10.67 mPa.s.

[0158] Experiment 1: Experimental steps and results of oil recovery by diluting polymer solution with wastewater injection in oil fields 1. Vacuum saturated water (1) Connect the outlet of artificial core A to the vacuum pump, close the inlet, check whether the oil level of the vacuum pump is qualified, and check the sealing of each connection part of the vacuum process.

[0159] (2) Turn on the vacuum pump. When the vacuum gauge on the vacuum pump shows below 0.09 MPa to 0.1 MPa, start continuous vacuuming for more than 8 h to 10 h.

[0160] (3) Close the outlet valve, connect the inlet to saturated water, and use a manual metering pump to pump saturated water into the core. Record the volume of water pumped out by the manual metering pump V1, the volume of water discharged from the core outlet V2, and the dead volume of the experimental process V3.

[0161] Measure the saturated water volume inside the core and calculate the effective pore volume of the core according to formula (i).

[0162] V P =V1-V2-V3----------------(i); V P ——Effective pore volume of the core, in cubic centimeters (cm 3 ); V1——The volume of water pumped out by the manual metering pump, in cubic centimeters (cm 3 ); V2——The amount of water discharged from the core outlet, in cubic centimeters (cm 3 ); V3——dead volume of experimental process, in cubic centimeters (cm 3 ).

[0163] The specific test results are shown in Table 11.

[0164]

[0165] 2. Saturated oil experiment After the saturated water experiment, the core was placed in a 45°C oven and the saturated oil experiment began. The simulated oil was injected into the Type II core A from the inlet end, and the saturated oil flow rate of Type II core A was 0.7 mL / min. The saturated oil experiment ended when the water volume in the outlet measuring cylinder no longer changed, and the accumulated saturated oil volume was measured, and the original oil saturation of the core was calculated according to formula (ii).

[0166]

[0167] ——The original oil saturation value of the core; ——The value of the cumulative saturated oil volume, in cubic centimeters (cm 3 ); ——The value of the total pore volume of the core, in cubic centimeters (cm 3 );

[0168] The oil-saturated core A was placed in a 45°C oven for constant temperature aging for at least 24 h.

[0169] 3. Water flooding experiment After the saturated oil experiment, the aging was carried out for more than 24 hours, and the water flooding experiment was started. The water flooding injection rate of the second type core A was 0.8mL / min, and the water flooding injection multiple was 1.5PV. The outlet was filled with a 100 mL measuring cylinder. At the end of the water flooding, the water content reached more than 98%, and the water flooding recovery rate was 40%~55% (it was unreasonable when the water flooding recovery rate was greater than 60%), and the water flooding was ended.

[0170] 4. Chemical flooding experiment Use the prepared oilfield reinjection wastewater to dilute the polymer solution for chemical flooding. The injection rate of chemical flooding for Class II core A is 0.3 mL / min, and the injection multiple is 1.0PV (according to the plan). The outlet is a 100 mL measuring cylinder to collect the liquid. Note that when the segment plugs alternate during the displacement process, top pressure injection is required. Note: The start time of the chemical flooding experiment is the day after the end of the water flooding. The recovery factor is calculated as follows: Recovery factor = oil volume / saturated oil volume V b .

[0171]

[0172] The results of the artificial core oil displacement experiment showed that when polyacrylamide with a weight-average molecular weight of 25 million was used as the chemical displacement polymer, the "dirty-dilution method" was used to prepare a polymer solution diluted with oilfield reinjection wastewater with a concentration of 1800 mg / L for oil displacement experiments. The recovery effect was 21.57%, the maximum pressure reached 1.5atm, and the total recovery rate was 65.69%.

[0173] Experiment 2: Nanobubble water mother liquor diluted polymer solution oil recovery experiment and results The experiment was carried out using core B. The experimental steps, data recording method and processing formula were the same as those of Experiment 1, except that the nanobubble water mother liquid obtained in Example 4 was used to dilute the polymer solution (i.e., nano-intelligent composite oil-displacing material) to carry out the oil displacement experiment. The experimental data and results are shown in Tables 14, 15 and 16, respectively.

[0174]

[0175]

[0176]

[0177] The experimental data in Tables 13 and 16 show that the recovery rate of the nano-intelligent composite oil-displacement material in Experiment 2 is 27.18%. Compared with the recovery rate of 21.57% of the polymer solution diluted with wastewater injected into the oil field, the absolute recovery rate is increased by 5.61% and the relative recovery rate is increased by 26.01%.

[0178] In Example 3, nanobubble water mother liquor was used alone for oil recovery, and the average recovery rate was increased by 2.79%; in Table 13, the polymer solution diluted with oilfield reinjection wastewater was used alone for oil recovery, and the recovery rate was increased by 21.57%. The recovery rate should be 24.36% (2.79% + 21.57%) by simple mathematical addition; in Table 16, the nano-intelligent composite oil recovery material increased the recovery rate by 27.18%, which is 2.82% higher than the sum of the recovery rates of the two materials used alone for oil recovery. It can be seen that the nanobubble water mother liquor and the polymer synergistic oil recovery have a synergistic effect.

[0179] The present invention provides a nano intelligent composite oil displacement material and its preparation method and application ideas and methods. There are many methods and ways to implement the technical solution. The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, without departing from the principle of the present invention, several improvements and modifications can be made, and these improvements and modifications should also be regarded as the protection scope of the present invention. All components not specified in this embodiment can be implemented by existing technologies.

Claims

1. A nanocomposite oil displacement material, characterized in that: The nanocomposite oil displacement material comprises nano bubble water mother liquid and polymer A; Wherein, the polymer A is an additionally added polyacrylamide; in the nanocomposite oil displacement material, the additionally added polyacrylamide has an addition concentration of 500-3000 ppm; The nano bubble water mother liquid is prepared by using oilfield reinjection wastewater as raw material through a cavitation-coupled electrochemical polarization process; The characteristic parameters of the nano bubble water mother solution are as follows: The diameter distribution range of the contained nanobubbles is 10 nm to 1000 nm; The concentration of nanobubbles contained is not less than 1.0×10 7 Pieces / mL; The pH value of the nanobubble water mother liquid is higher than the pH value of the oilfield reinjection wastewater by more than 0.25; The content of divalent iron is not higher than 1.0 mg / L; The divalent sulfur content is not higher than 2.0 mg / L; The sulfate-reducing bacteria content is not higher than 100 / mL; The content of saprophytic bacteria is not higher than 100 / mL; The iron bacteria content is not higher than 100 / mL.

2. The nanocomposite oil displacement material according to claim 1, characterized in that: It also includes other dilution water; the other dilution water is any one or a combination of two of oilfield reinjection wastewater and clean water; the volume ratio of the other dilution water to the nano bubble water mother liquid is 10%~90%:

1.

3. The nanocomposite oil displacement material according to claim 1, characterized in that: The nano bubble water mother liquid is prepared by using oilfield reinjection wastewater as raw material through a cavitation coupled electrochemical polarization process using a cavitation coupled electrochemical polarization device; The cavitation-coupled electrochemical polarization device comprises a polarization tank (1), a polarization electrode (2), a raw material feed pipeline (3), a raw material pump (4), a raw material feed pipe (5), a polarization controller (6), a polarization electrode control line (7), an ozone generator (8), an ozone delivery pipeline (9), a venturi drainage pipe (10), a polarization liquid circulation pipeline (11), a circulation pump (12), a dirty oil overflow and decontaminated oil pipe port (13), a sampling and product collection port (14), a composite quantum dot material raw material tank (15), a plunger pump (16) and a composite quantum dot material injection pipeline (17); in, A polarization electrode (2) is arranged inside the polarization tank (1), the cathode of the polarization electrode (2) is connected to the negative electrode of the polarization controller (6) through the polarization electrode control line (7), and the anode of the polarization electrode (2) is connected to the positive electrode of the polarization controller (6) through the polarization electrode control line (7); The raw material incoming pipeline (3) is connected to the raw material pump (4), and the raw material pump (4) is connected to the raw material inlet pipe (5) of the polarization tank through a connecting pipe; the inlet end of the raw material inlet pipe (5) of the polarization tank is located outside the polarization tank (1), and the outlet end is located at the bottom of the polarization tank (1); The inlet end of the venturi drainage pipe (10) is located outside the polarization tank (1), and the outlet end is located at the bottom of the polarization tank (1); the spray direction of the venturi drainage pipe (10) is from the inlet end to the outlet end; and a reverse overflow facility is provided at the bottom of the polarization tank (1) at the outlet end of the venturi drainage pipe (10); The ozone generator (8) is connected to the throat of the Venturi drainage tube (10) via an ozone delivery pipeline (9) and is used to deliver an air-ozone mixed gas; The inlet and outlet of the composite quantum dot material raw material tank (15), the plunger pump (16), the composite quantum dot material injection pipeline (17), the polarization liquid circulation pipeline (11), and the venturi drainage tube (10) are connected in sequence; the composite quantum dot material injection pipeline (17) is connected to the polarization liquid circulation pipeline (11); The upper part of the side wall of the polarization tank (1) is provided with a dirty oil overflow and dirty oil removal pipe port (13); the middle part of the side wall of the polarization tank (1) is provided with a sampling and product collection port (14); the lower part of the side wall of the polarization tank (1) is provided with a circulating liquid outlet connected to a circulating pump (12) through a pipeline, and the circulating pump (12) is connected to the inlet of the Venturi drainage pipe (10) through a polarization liquid circulation pipeline (11).

4. The nanocomposite oil displacement material according to claim 3, characterized in that: The nanobubble water mother liquid is prepared by using oilfield reinjection wastewater as raw material through a cavitation coupled electrochemical polarization device to perform a cavitation coupled electrochemical polarization process. The specific steps are as follows: The oilfield reinjection wastewater is pumped into the raw material inlet polarization tank pipe (5) through the raw material feed pipeline (3) by the raw material pump (4) until it enters the polarization tank (1); when the liquid level of the oilfield reinjection wastewater in the polarization tank (1) reaches the sampling and product extraction port (14), the polarization controller (6) is started to adjust the working voltage and working current so that the polarization electrode (2) works to polarize the oilfield reinjection wastewater. After bubbles overflow from the surface of the polarization electrode (2), the circulation pump (12) is started; the circulation pump (12) circulates the oilfield reinjection wastewater in the polarization tank (1) into the polarization liquid circulation pipeline (11) until it reaches the inlet end of the Venturi drainage pipe (10), and further sprays it into the polarization tank (1); after the circulation pump (12) works stably, the ozone generator (8) and the plunger pump (16) are started respectively to inject the composite quantum dot material raw material tank (15) with the ozone generator (8) and the plunger pump (16). The composite quantum dot material in the venturi drainage tube (10) is pumped into the inlet of the venturi drainage tube (10) by a plunger pump (16), and is further introduced into the polarization tank (1) through the injection of the venturi drainage tube (10); at the same time, when the circulating pump (12) draws out the oilfield reinjection sewage from the polarization tank (1) and pumps it into the inlet end of the venturi drainage tube (10), and further injects it into the polarization tank (1), a pressure difference is generated at the throat of the venturi drainage tube (10), thereby introducing the air-ozone mixed gas, and the cavitation process of the venturi drainage tube (10) forms an ozone fine bubble jet flow, which is ejected from the outlet end, and the ejected fluid overflows in the reverse direction through the reverse overflow facility at the bottom of the polarization tank (1) at the outlet end of the venturi drainage tube (10), flows through the polarization electrode (2) for electrochemical polarization, and after the cavitation-coupled electrochemical polarization process is completed, a nano bubble water mother liquid is obtained.

5. The nanocomposite oil displacement material according to claim 4, characterized in that: The composite quantum dot material is a sulfur-doped carbon quantum dot material, which uses sulfur powder as a sulfur source and carboxymethyl cellulose as a carbon source. The sulfur powder and carboxymethyl cellulose are dispersed in an alkaline solution to obtain a dispersion, and then oxygen is introduced to heat the dispersion for reaction, and then the dispersion is post-treated to obtain the sulfur-doped carbon quantum dot material. The amount of the composite quantum dot material added is based on the amount of oilfield reinjection wastewater treated, and the amount added is 2.5-7.5 mg / kg of oilfield reinjection wastewater.

6. The nanocomposite oil displacement material according to claim 4, characterized in that: The cathode of the polarizable electrode (2) is made of a titanium alloy; the anode of the polarizable electrode (2) has a base material of a titanium alloy, the surface of the titanium alloy is chemically plated, and the coating is platinum or ruthenium-iridium alloy; the operating voltage is 3.0-48.0 V; the operating current is 1.0-150.0 A / m 3 .

7. The nanocomposite oil displacement material according to claim 4, characterized in that: The gas source of the ozone generator (8) is air; the concentration of ozone in the air-ozone mixed gas is 5-30 mg / L; the volume ratio of the air-ozone mixed gas to the oilfield reinjection wastewater in the polarization tank is 5%-20%:

1.

8. The nanocomposite oil displacement material according to claim 1, characterized in that: The nano composite oil displacement material has a viscosity retention rate of not less than 94.00% after being stored for 15 days, a viscosity retention rate of not less than 90.00% after being stored for 30 days, and a viscosity retention rate of not less than 75.00% after being stored for 90 days under the condition of being isolated from air.

9. The method for preparing the nanocomposite oil displacement material according to any one of claims 1 to 8, characterized in that: The nano bubble water mother liquid and polymer A are mixed evenly to obtain a nano composite oil displacement material; or, Mix other dilution water, nano bubble water mother liquid and polymer A to obtain nano composite oil displacement material; The other dilution water is any one of oilfield reinjection wastewater and clean water or a combination of the two.

10. Use of the nanocomposite oil displacement material according to claim 1 in oil production.

Citation Information

Patent Citations

  • Multifunctional cellulose-based sulfur quantum dot and application

    CN117603678A

  • Preparation device, preparation method and application of nanobubble oil displacement material

    CN118217834A